THE EFFECT OF FERMENTED DRAGON FRUIT (Hylocerus polyrhizus) PEEL IN THE RATION ON CARCAS AND CHOLESTEROL PRODUCTION IN THE BLOOD OF 2-10 WEEKS AGE NATIVE CHICKENS - N. P. M., Suartiningsih; Aryawan, I N. A. (Jurnal Peternakan Tropika; Vol 12 No 6 (2024): Vol. 12 No. 6 Year 2024; November - Desember, 2024)
This study aimed to examine the effect of fermented dragon fruit peel flour ( Hylocereus polyrhizus ) using Saccharomyces cerevisiae on the carcass production of native chickens. The experiment was conducted over 10 weeks using a Completely Randomized Design (CRD) with four treatments and five replications. Each replication consisted of 10 native chickens, resulting in a total of 200 chickens used in the study. The treatments included R0 (feed without fermented dragon fruit peel flour), R1 (feed with 5% fermented dragon fruit peel flour), R2 (feed with 7% fermented dragon fruit peel flour), and R3 (feed with 9% fermented dragon fruit peel flour). Observed variables included slaughter weight, carcass weight, carcass percentage, and carcass cut percentage. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s multiple range test if significant differences were observed ( P <0.05). The results showed that treatments R0, R1, R2, and R3 did not significantly affect ( P >0.05) slaughter weight, breast weight, wing weight, back weight, slaughter weight percentage, thigh percentage, breast percentage, or wing percentage. However, significant effects ( P <0.05) were observed on carcass weight, thigh weight, carcass percentage, and blood cholesterol levels. Based on these findings, it can be concluded that incorporating up to 9% fermented dragon fruit peel flour in the feed positively influences carcass weight, carcass percentage, and reduces blood cholesterol levels, but does not affect the weight and percentage of other carcass cuts.